Pengaruh Internship Experience, Soft Skill dan Hard Skill Terhadap Kesiapan Kerja - Warnanti Arie Luthfiani; M. Farid Wajdi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to evaluate the impact of Internship Experience, Soft Skills, and Hard Skills on Job Readiness (a study on students of Universitas Muhammadiyah Surakarta). A quantitative approach was employed to examine the student population at the university, involving 150 respondents selected using purposive sampling techniques. Data were collected through an online questionnaire distributed via Google Forms and analyzed using SmartPLS 3.0. The results reveal that internship experience, soft skills, and hard skills positively and significantly influence students' job readiness. The research model demonstrated a good Goodness of Fit, with path coefficients indicating a significant contribution of each independent variable to job readiness. These findings underscore the critical importance of developing soft and hard skills during university years to better prepare students for the workforce.